Demographic alternatives for aging industrial countries: increased total fertility rate, labor force participation, or immigration - Robert Holzmann (Institute for the Study of Labor (IZA), 2005)
The paper investigates the demographic alternatives for dealing with the projected population aging and low or negative growth of the population and labor force in the North. Without further immigration, the total labor force in Europe and Russia, the high-income countries of East Asia and the Pacific, China, and, to a lesser extent, North America is projected to be reduced by 29 million by 2025 and by 244 million by 2050. In contrast, the labor force in the South is projected to add some 1.55 billion, predominantly in South and Central Asia and in Sub-Saharan Africa. The demographic policy scenarios to deal with the projected shrinking of the labor forth in the North include moving the total fertility rate back to replacement levels, increasing labor force participation of the existing population through a variety of measures, and filling the demographic gaps through enhanced immigration. The estimations indicate that each of these policy scenarios may partially or even fully compensate for the projected labor force gap by 2050. But a review of the policy measures to make these demographic scenarios happen also suggests that governments may not be able to initiate or accommodate the required change.
Keywords: J11; I38; Q15; 330; demographic policy; aging; fertility rate; labor force; migration; Alternde Bevölkerung; Bevölkerungspolitik; Migrationspolitik; Arbeitsmarktpolitik; Beschäftigungspolitik; Wirkungsanalyse; Vergleich; Industriestaaten; Welt